2010
DOI: 10.1007/s11250-010-9617-z
|View full text |Cite
|
Sign up to set email alerts
|

Coprological prevalence and intensity of helminth infection in working horses in Lesotho

Abstract: This study aimed to (1) estimate infection prevalence of strongyle, Oxyuris equi and Parascaris equorum species and the intensity of infection with strongyles in working horses in lowland Lesotho and (2) investigate associations between infection and horse age, sex and owner-reported use of anthelmintics. In a cross-sectional survey, fresh faecal samples were obtained from 305 randomly selected horses and worm egg counts performed using a validated field laboratory kit. Details of anthelmintic use were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
6
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
3
23
6
4
Order By: Relevance
“…Study conducted in Western highlands of Oromia, Ethiopia indicated 2.1% prevalence of Oxyuris equi in horses [11]. Similar study in Lesotho showed slight higher prevalence (6.2%) in horses [28]. The lowest prevalence might be due to the effect of relative higher temperature in the present study area which desiccates the highly susceptible Oxyuris equi egg.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Study conducted in Western highlands of Oromia, Ethiopia indicated 2.1% prevalence of Oxyuris equi in horses [11]. Similar study in Lesotho showed slight higher prevalence (6.2%) in horses [28]. The lowest prevalence might be due to the effect of relative higher temperature in the present study area which desiccates the highly susceptible Oxyuris equi egg.…”
Section: Discussionsupporting
confidence: 58%
“…This result is higher than the prevalence reported in Ethiopia by Yoseph et al [29], Fikru et al [11], Getachew et al [30] who reported 15.7%, 7.3%, and 16.2%, respectively and in Lesotho by Melissa et al [28] who reported 21.6% in horses. The prevalence of Parascaris equorum was 42.29% in donkeys in the present study is higher than 15.7% and 17.3% reported by Yoseph et al [21] and Fikru et al [11] in donkeys.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This has been mentioned in literatures [26]. Upjohn et al [27] revealed that there seemed to be an inverse association between age and intensity of strongyle infection, i.e., as horses gets older, the odds of higher egg count are reduced.…”
Section: Discussionmentioning
confidence: 83%